2019
DOI: 10.1136/esmoopen-2019-000536
|View full text |Cite
|
Sign up to set email alerts
|

Ex vivo lung cancer spheroids resemble treatment response of a patient with NSCLC to chemotherapy and immunotherapy: case report and translational study

Abstract: IntroductionIn the era of precision medicine, research studies are aiming to design patient-tailored treatment strategies. In this work, we present a clinical case of a patient with non-small cell lung cancer (NSCLC) accompanied by a translational study with the intent to assess the correspondence of drug sensitivity in ex vivo spheroidal tumour cultures and peripheral blood biomarkers with clinical outcome.MethodsPrimary tumour tissue, patient-derived tumour spheroids, peripheral blood mononuclear cells and c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(24 citation statements)
references
References 18 publications
0
24
0
Order By: Relevance
“…Lagies et al found that 3D spheroid cultures shared strikingly metabolic similarities to the organ tissue such that authors suggested optimised 3D culture techniques could possibly replace animal testing [ 51 ]. Furthermore, Di Liello et al cultured 3D spheroids from patient derived non-small cell lung cancer tumours for ex-vivo analysis [ 52 ]. Authors reported that drug sensitivities to cisplatin-based chemotherapy and anti-programmed death 1 drug sensitivity were consistent from the patient clinical response to 3D culture.…”
Section: Discussionmentioning
confidence: 99%
“…Lagies et al found that 3D spheroid cultures shared strikingly metabolic similarities to the organ tissue such that authors suggested optimised 3D culture techniques could possibly replace animal testing [ 51 ]. Furthermore, Di Liello et al cultured 3D spheroids from patient derived non-small cell lung cancer tumours for ex-vivo analysis [ 52 ]. Authors reported that drug sensitivities to cisplatin-based chemotherapy and anti-programmed death 1 drug sensitivity were consistent from the patient clinical response to 3D culture.…”
Section: Discussionmentioning
confidence: 99%
“…Most importantly, the responses to NAT in organoids paralleled the patients’ progression-free survival after surgical resection [ 107 ]. Similarly, Di-Liello and colleagues utilized a lung cancer spheroid model to show their utility in predicting the response to chemo and immune therapies [ 108 ]. These studies represent a significant advance in utilization of organoid cultures as a functional tool in predicting response to treatment and could be leveraged by clinicians to personalize therapies.…”
Section: Applications Of Patient-derived Organoids and Spheroidsmentioning
confidence: 99%
“…Di Liello et al could demonstrate a reproduction of patient tumor response to chemotherapy by using a spheroid model derived from a non-small cell lung cancer biopsy. This model of spheroid was generated from the cell suspension from the tumor digestion culture on an extracellular matrix (Matrigel) ( 48 ). Although tissue digestion preserves tumor cell interaction, the architecture of the tissue is lost and the loss of stromal cells.…”
Section: D Modelsmentioning
confidence: 99%